Face Contour is Crucial to the Fat Face Illusion. (May 2013) - Sun, Yu-Hao; Quinn, Paul C; Wang, Zhe; Shi, Huimin; Zhong, Ming; Jin, Haiyang; Ge, Liezhong; Pascalis, Olivier; Tanaka, James W; Lee, Kang
In 2010 Thompson reported a "fat face thin" illusion that, when next to an inverted face, an upright face looks "fatter". Sun et al (2012 Perception 41 117–120) observed that one of the faces need not be inverted for the illusion to emerge: When two identical faces are presented one above the other, the face at the bottom appears "fatter" than the top one. Neither inverted faces nor clocks induced the illusion. Here we conducted three experiments probing the role that face contour plays in producing the fat face illusion. In experiment 1 line drawing faces were found to induce the illusion, suggesting that face contour is important for producing the illusion. In experiment 2 line drawing faces with scrambled internal features and empty line drawing faces devoid of internal features were found to induce the illusion. In experiment 3 internal face features arranged in their canonical face layout, but not in a scrambled layout, were found to induce the illusion. However, the magnitude of the effect was significantly weaker than the effect obtained for empty face contour in experiment 2. Collectively, these results suggest that a fat face illusion is obtained when there is sufficient information in the stimulus to activate an internal face schema.